Scratch based graphical programming online guide/exam system - Chan, Bryan Hong Ming (2019)
Over the past couple of years, there has been an increase in interest in Computer Science due to various new innovations such as cryptocurrency, block chain and many more. As such, more and more students from different background are trying to pick up Computer Science. Some students may have no issue picking up programming while others may have difficulty and lose interest in programming. While it is sometimes the task of the instructor to keep students motivated and interested in learning, it cannot be helped if the contents and fundamentals of the topics are uninteresting to students. This project aims to find alternatives to teach programming while building interest in students so that they have the motivation to continue to learn programming.